Pengaruh Independensi, Pengalaman, Due Profesiional Care, Dan Akuntabilitas Terhadap Kualitas Audit (Studi Empiris pada Kantor Akuntan Publik di Semarang) - Arroyyani, Shiela Nazila, Drs. Yuli Tri Cahyono , M.M., Akt., CA (2015)
This research aims to test the influence of the independence, experience, due professional care, an audit on quality and accountability in the area of Semarang. Based on the results of the study are expected to provide an overview of the dynamics that occur in public accounting in particular the auditor in carrying out its work. This research included in this type of quantitative research using the survey directly through questionnaires. The population in this research is the auditor who worked in the Office of public accountant in Semarang. The techniques used in sampling was convenience sampling. Data collection using the questionnaire which had tested the level of validity and reliability. Technique of data analysis using multiple regression test, test, test the determination of the coefficient F R2 and t-test. The results showed that: (1) effect on the independence significance of the audit quality. (2) affects the quality significance of auditing Experience. (3) the Due professional care have an effect significance on the quality of audits. (4) Accountability significance of audit quality. Keywords: independence, due professional care, experience, accountability, and quality auditing.